Demonstration of reentrant relaxor ferroelectric phase transitions in antiferroelectric-based (Pb0.50Ba0.50)ZrO3 ceramics - Pokharel B.P.; Shrestha L.K.; Ariga K.; Pandey D. (My University, 2025)
Herein we demonstrate a novel (Pb0.50Ba0.50)ZrO3 (PBZ50) ceramic that exhibits a reentrant relaxor ferroelectric phase transition in an antiferroelectric-based perovskite system. The dielectric measurement has confirmed that the imaginary part of the dielectric constant for the reentrant phase is nearly frequency independent below the freezing temperature. The reentrant behavior could be scaled to a phenomenological equation involving the Vogel-Fulcher relationship. These results were further complemented by the polarization measurements. The PBZ50 was fabricated using a semi-wet synthetic route involving a solid-state thermochemical reaction. We believe this unusual phase transition sequence in the PBZ50 material would be highly useful in high-density data storage devices. © 2018 by the authors.